Antiproliferation of Berberine in Combination with Fluconazole from the Perspectives of Reactive Oxygen Species, Ergosterol and Drug Efflux in a Fluconazole-Resistant Candida tropicalis Isolate - Shao, Jing; Shi, GaoXiang; Wang, TianMing; Wu, DaQiang; Wang, ChangZhong (Frontiers in Microbiology, 2016)
Candida tropicalis has emerged as an important pathogenic fungi in nosocomial infections due to its recalcitrant resistance to conventional antifungal agents, especially to fluconazole (FLC). Berberine (BBR) is a bioactive herbal-originated alkaloids and has been reported to possess antifungal functions against Candida albicans. In this paper, we tried to figure out the antifungal mechanisms of BBR and/or FLC in a clinical C. tropicalis isolate 2006. In the microdilution test, the minimum inhibitory concentration (MIC) of BBR was found 16 μg/mL with fractional inhibitory concentration index (FICI) 0.13 in C. tropicalis 2006. The synergism of BBR and FLC was also confirmed microscopically. After the treatments of BBR and/or FLC, the studies revealed that (i) FLC facilitated BBR to increase reactive oxygen species (ROS), (ii) FLC enhanced the intranuclear accumulation of BBR, (iii) BBR decreased the extracellular rhodamine 123 (Rh123) via inhibiting efflux transporters, (iv) FLC assisted BBR to reduce ergosterol content, and (v) BBR in combined with FLC largely downregulated the expressions of Candida drug resistance 1 (CDR1) and CDR2 but impact slightly multidrug resistance 1 (MDR1), and upregulate the expression of ergosterol 11 (ERG11). These results suggested that BBR could become a potent antifungal drug to strengthen FLC efficacy in FLC-resistant C. tropicalis via ROS increase, intracellular BBR accumulation, ergosterol decrease and efflux inhibition.